Palace Flop House and Grill - Peter Stackpole:::Creator::::::::::::
Palace Flop House and Grill. Harold Otis 'Gabe' Bicknell (model for 'Mack' in Cannery Row) is shown climbing the stairs. See also number 157. RESTRICTED USE Originals is in the safe, 2 copies, (no copy is in photo files.)